2018
DOI: 10.1038/s41440-018-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endothelial nitric oxide synthase reverses the effect of exercise on improving cognitive function in hypertensive rats

Abstract: Hypertension-induced endothelial dysfunction is associated with β-amyloid (Aβ) deposition, a typical pathology of Alzheimer's disease (AD). Endothelial nitric oxide synthase (eNOS) phosphorylation, impaired by phosphatidylinositol 3-kinase (PI3K)/protein kinase-B(Akt) pathway abnormalities in hypertensive rats, has a critical role in endothelial function. However, it is unknown whether eNOS participates in the hypertension-induced pathology of AD. In this study, we investigated the role of eNOS in Aβ depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As the most commonly used animal models, data collection on rats and mice benefit from their short gestation periods and numerous off-spring. A number of modalities of exercise training such as treadmill running, voluntary wheel running, and swim training have been utilized on rat and mice models of various genetic backgrounds [9,4548].…”
Section: Principle Of Animal Exercise Training Protocols and Sample Cmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most commonly used animal models, data collection on rats and mice benefit from their short gestation periods and numerous off-spring. A number of modalities of exercise training such as treadmill running, voluntary wheel running, and swim training have been utilized on rat and mice models of various genetic backgrounds [9,4548].…”
Section: Principle Of Animal Exercise Training Protocols and Sample Cmentioning
confidence: 99%
“…Several animal models and human epidemiological studies support the cardio-protective effect of exercise [46]. Several protective mechanisms demonstrated that exercise increased VO 2max (maximal oxygen consumption), improved cardiorespiratory fitness (CRF) [7], lipid profile [8], endothelial function [9], increased number of capillaries [10], and mitochondria anti-oxidant activity in the cardiovascular system [11]. However, while exercise typically results if beneficial effects on heart function, there are occasions when it could result in unexpected death during exercise especially for the CVD cohort [1214].…”
Section: Introductionmentioning
confidence: 99%
“…NO is a reactive gas secreted in endothelial cells by the endothelial isoform of the enzyme NO synthase, and is tonically released to control systemic vascular tone and neuronal activity in the CNS [93]. In chronic cerebral hypoperfusion models of VCI [94] and in hypertensive rats [95], it has been observed that the bioavailability of endothelium-derived NO is reduced, and that this reduction may be the cause of cognitive deficits. Further support to this hypothesis comes from studies in AD animal models, where a reduction of NO increases the negative effects of amyloid beta (Aβ) on cognition, whereas the administration of NO has a protective effect on Aβ deposition [96].…”
Section: Molecular Mechanism Of Vcimentioning
confidence: 99%
“…Many studies are now concentrating on treatments aimed at restoring NO levels at normal conditions in VCI models [92,95,97].…”
Section: Molecular Mechanism Of Vcimentioning
confidence: 99%
“…Spontaneously hypertensive stroke-prone (SHRSP) rat is a well-recognized animal model of lacunar stroke and essential hypertension in humans (17)(18)(19). These rats are also an important model for studying attention deficit hyperactivity disorder (20)(21)(22)(23), and Alzheimer's related vascular pathology (24,25) in humans. The SHRSP rats exhibit multiple dysfunctions such as saltsensitive spontaneous hypertension, cortical lesions with a high incidence of stroke by ;16 wk of age, nephropathy, hyperactivity of the renin-angiotensin system, insulin resistance, and hypertriglyceridemia (17,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%